2020
DOI: 10.1093/molehr/gaaa069
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model reveals the events and underlying regulatory signals during the gonadotrophin-dependent phase of follicle development

Abstract: During folliculogenesis, the gonadotrophin-dependent phase begins at the small antral follicle stage and ends with Graafian follicles. In this study, pregnant mare’s serum gonadotrophin was used to induce gonadotrophin-dependent folliculogenesis in mice, following which the developmental events that follicles undergo, as well as the underlying regulatory signals, were investigated at both the morphological and transcriptomic level. Gonadotrophin-dependent folliculogenesis consisted of three phases: preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…Granulosa cells apoptosis or survival is considered as a signal for follicle development and oocyte growth, thus granulosa cells are essential for cell proliferation, follicular development, oocyte maturation, follicle ultimately ovulates or undergoes atresia ( Matsuda et al, 2012 ; Choi et al, 2011 ; Tanabe et al, 2015 ; Kadariya et al, 2015 ; Chen et al, 2020 ). Even the granulosa cells state could determine the fate of follicle, mainly due to its effect on synthesize of steroids, growth factors, and cytokines, which have been proved to be essential for oocytes mature and follicle development ( Matsuda et al, 2012 ; M’baye et al, 2015 ; Wang et al, 2017a , 2018 ; Chen et al, 2020 ). Therefore, improving the granulosa cells functions become very important for acting its physiological role during oocytes mature and follicle development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Granulosa cells apoptosis or survival is considered as a signal for follicle development and oocyte growth, thus granulosa cells are essential for cell proliferation, follicular development, oocyte maturation, follicle ultimately ovulates or undergoes atresia ( Matsuda et al, 2012 ; Choi et al, 2011 ; Tanabe et al, 2015 ; Kadariya et al, 2015 ; Chen et al, 2020 ). Even the granulosa cells state could determine the fate of follicle, mainly due to its effect on synthesize of steroids, growth factors, and cytokines, which have been proved to be essential for oocytes mature and follicle development ( Matsuda et al, 2012 ; M’baye et al, 2015 ; Wang et al, 2017a , 2018 ; Chen et al, 2020 ). Therefore, improving the granulosa cells functions become very important for acting its physiological role during oocytes mature and follicle development.…”
Section: Discussionmentioning
confidence: 99%
“…The luteinization of granulosa cells is essential for pregnancy maintenance, which is a temporary organ for secretion of progesterone ( He et al, 2016a ). During follicles development, granulosa cells completed the preparations for proliferation and differentiation, shifted energy metabolism to glycolysis, and follicles acquired the capacity for estradiol secretion and ovulation ( Chen et al, 2020 ). The granulosa cells within the follicle accompanied by the proliferation, differentiation, and apoptosis during the reproductive period ( Chowdhury et al, 2016 ; Denkova et al, 2014 ; Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fshr and Lhcgr act as antennas on the follicle, where they are responsible for receiving gonadotropin signals from the pituitary gland [ 29 , 30 , 31 ]. In the current study, we found that both Fshr and Lhcgr were gradually upregulated at the early stage of folliculogenesis; soon afterwards, they underwent a period of rapid increase and then reached a plateau.…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect observed in the study is the potential association of melatonin and MT1 with LH. LH plays a pivotal role in oocyte maturation (Fan et al, 2008;Zamah et al, 2010;Arroyo et al, 2020;Chen et al, 2020;Liu et al, 2020). LH is similar to melatonin, which can lower the concentration of cAMP within the oocyte but has different mechanisms than melatonin (Sethi et al, 2008;Muhlbauer et al, 2011;Lyga et al, 2016).…”
Section: Discussionmentioning
confidence: 99%